2008
DOI: 10.1111/j.1464-0597.2008.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

To Identify or Not To Identify? National Disidentification as an Alternative Reaction to Perceived Ethnic Discrimination

Abstract: This study was a longitudinal investigation of the psychological and attitudinal consequences of perceived ethnic discrimination and ethnic and national identification among immigrants in an 8-year follow-up study with panel data. The participants were 293 immigrants in Finland coming from the former Soviet Union. The results supported the Rejection-Disidentification Model (RDIM) proposed in this study; perceived discrimination resulted in national disidentification, which, in turn, increased hostile attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
372
5
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(425 citation statements)
references
References 40 publications
39
372
5
9
Order By: Relevance
“…Two pre-existing measures of perceived discrimination (Schmitt, Spears, & Branscombe, 2003), validated also in the intergroup context of this study (Jasinskaja-Lahti et al, 2009), were adapted for use in the pre-and postmigration stages. Response options of all four items ("Finns will have/have a positive attitude towards my ethnic background," "I will be/have been treated fairly in Finland," "I will experience/have experienced discrimination in Finland," "My ethnic background will be/is appreciated in Finland") ranged from 1 = strongly disagree to 5 = strongly agree, with higher scores denoting higher levels of anticipated (T …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two pre-existing measures of perceived discrimination (Schmitt, Spears, & Branscombe, 2003), validated also in the intergroup context of this study (Jasinskaja-Lahti et al, 2009), were adapted for use in the pre-and postmigration stages. Response options of all four items ("Finns will have/have a positive attitude towards my ethnic background," "I will be/have been treated fairly in Finland," "I will experience/have experienced discrimination in Finland," "My ethnic background will be/is appreciated in Finland") ranged from 1 = strongly disagree to 5 = strongly agree, with higher scores denoting higher levels of anticipated (T …”
Section: Methodsmentioning
confidence: 99%
“…We aim to simultaneously test the effects of all three types of premigration expectations and anticipations (i.e., stress, sociocultural difficulties, and discrimination) on postmigration psychological adaptation among ethnic migrants. Importantly, previous research has attested that immigrants with elevated levels of psychological stress symptoms also may face other difficulties, such as prejudice or sociocultural difficulties (e.g., Jasinskaja-Lahti, 2008; Jasinskaja-Lahti, Liebkind, & Solheim, 2009;Masgoret & Ward, 2006). Thus, in our analysis, we acknowledge that the different dimensions of acculturation may be interrelated so that difficulties in one dimension correlate positively with difficulties in others (see also Berry, 2006;Masgoret & Ward, 2006).…”
Section: Acculturation and Adaptationmentioning
confidence: 99%
“…It should also be noted that, as is often the case in social and behavioural sciences, causal chains are reciprocal: perceived discrimination affects identification and compromises well-being, while worsened psychological health and a strong ethnic acculturation profile predispose to less favourable perceived intergroup relations (Jasinskaja-Lahti et al, 2009;Zagefka & Brown, 2002). In addition, the strength of ethnic identification may determine how severe the ramifications of discrimination are.…”
Section: Identities and Well-being In Contextmentioning
confidence: 99%
“…For example in Finland, instead of increasing ethnic identification, Russian-speaking immigrants were found to react to perceived discrimination with disidentification from the national majority group (i.e., Jasinskaja-Lahti et al, 2009;Jasinskaja-Lahti, colleagues (2009; have suggested the Rejection-Dis-identification model (RDIM) according to which perceived discrimination prevents minority members from developing a sense of belonging to a national superordinate group and further leads to more negative attitudes towards the majority group members.…”
Section: Identities and Well-being In Contextmentioning
confidence: 99%
“…Sociological studies look at whether minority members who feel discriminated against identify more strongly with their country of origin or less strongly with their host country (deVroome et al 2014, Diehl et al 2016, Jasinskaja-Lahti et al 2009, Martinovic and Verkyten 2012, Skrobanek 2009, Verkuyten and Yildiz 2007, are more likely to plan to return to their country of origin (San Pierre et al 2015), are more religious and slower to acculturate Phalet 2012, Maliepaard andAlba 2016), are more involved in transnational activities (Snel at al 2016), are more politically involved (Fischer-Neumann 2014, Fleischmann et al 2011, have less trust in mainstream institutions (Röder and Mühlau 2012), have fewer native friends (Schacht et al 2014), or show higher levels of criminal behavior (Burt et al 2012). Studies rarely focus on the link between PD and integration in the educational system (Berkel et al 2010) or the labor market (Koopmans 2016), partly because these aspects of integration can be investigated more reliably using census rather than other survey data, and the former does not include measures of perceived discrimination.…”
Section: Linking Perceived Discrimination and Integration: Existing Fmentioning
confidence: 99%